2023
DOI: 10.3390/jmse11071324
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Methods of Measurement, Optimization and Forecast of Propulsion Shaft Bearing Load of Ships

Abstract: The qualit12y of shafting alignment is related to the reliability and safety of a ship’s operation, and bearing displacement adjustment (BDA) plays a key role in shafting alignment. To solve the problems encountered in ship shafting alignment in the actual construction, this study focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Li et al (2023) 7) focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the bearing load influence coefficients (BICs) to forecast the load after the adjustment. The experimental work, as well as the measurement, calculation and analysis of several real ships, indicated that the measurement, optimization and forecasting methods of the bearing load of the propulsion shafting of large ships in this study would be significant for guiding the actual construction work of ship shafting alignment.…”
Section: Kim Et Al (2021)mentioning
confidence: 99%
“…Li et al (2023) 7) focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the bearing load influence coefficients (BICs) to forecast the load after the adjustment. The experimental work, as well as the measurement, calculation and analysis of several real ships, indicated that the measurement, optimization and forecasting methods of the bearing load of the propulsion shafting of large ships in this study would be significant for guiding the actual construction work of ship shafting alignment.…”
Section: Kim Et Al (2021)mentioning
confidence: 99%
“…Strain measurement is yet another indirect method for measuring bearing offset. The principle is to theoretically calculate the influence coefficient of each bearing offset on the shaft's bending moment, then install strain gauges on the shaft to measure the change in the shaft's bending moment under different operating conditions, and finally invert the bearing offset [1,[16][17][18][19]. Adopting the wireless transmission device can alleviate the difficulty of data collection when the shaft is rotating.…”
Section: Introductionmentioning
confidence: 99%